PERAN ORANG TUA DALAM PENGUATAN AKTIVITAS BERIBADAH ANAK DI MASA PANDEMI COVID-19 - Ummah, Ika Zuharotul (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
The Covid-19 pandemic has had many impacts on several sectors of life, one of which is the education sector. The online school policy does not only have an impact on learning, but also on worship habituation activities that previously existed in schools being shifted to being at home. In this case, parents as the main educators in the family have a role in strengthening children's worship activities during the pandemic.The purposes of this study are: (1) To describe the role of fathers and mothers in strengthening children's worship activities during the Covid-19 pandemic, (2) To describe the steps taken by fathers and mothers when children disobey, (3) To describe the inhibiting factors faced by families in strengthening children's worship activities during the Covid-19 pandemic.This research uses a qualitative approach with the type of case study research. Data collection techniques in this study used observation, interviews, and documentation techniques. The data that has been obtained is then analyzed by steps, namely data reduction, data presentation, and drawing conclusions. The validity of the data in this study used triangulation techniques and source triangulation techniques.The results showed that: (1) The Role of Parents in Strengthening Children's Worship Activities During the Covid-19 Pandemic, among others: a) As a motivator, b) As Uswah, c) As a facilitator, d) As a mentor; (2) Steps taken by parents when a child disobeys, among others: a) Be firm, b) Apply rules and consequences if the child violates, c) Ask the Teacher for Help to Advise; (3) Inhibiting factors in Strengthening Children's Worship Activities During the Covid-19 Pandemic, including: a) The influence of peers, b) The influence of gadgets, c) The child's mood fluctuates. Parents are expected to build good cooperation with teachers so that the habit of worship that previously existed at school can be carried out at home to the fullest. Abstrak Pandemi Covid-19 membawa banyak pengaruh bagi beberapa sektor kehidupan, salah satunya sektor pendidikan. Kebijakan sekolah daring tidak hanya berdampak pada pembelajaran saja, namun pada kegiatan-kegiatan pembiasaan ibadah yang sebelumnya ada di sekolah dialihkan menjadi di rumah. Dalam hal ini, orang tua sebagai pendidik utama di keluarga memiliki peran dalam penguatan akativitas beribadah anak di masa pandemi. Tujuan Penelitian ini adalah untuk: (1) Untuk mendeskripsikan peran ayah dan ibu dalam penguatan aktivitas beribadah anak di masa pandemi Covid-19, (2) Untuk mendeskripsikan langkah-langkah yang yang diambil ayah dan ibu ketika anak tidak menurut, (3) Untuk mendeskripsikan faktor penghambat yang dihadapi keluarga dalam penguatan aktivitas beribadah anak di masa pandemi Covid-19. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Teknik pengumpulan data dalam penelitian ini menggunakan teknik observasi, wawancara, dan dokumentasi. Data yang telah diperoleh kemudian dianalisis dengan langkah-langkah yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Adapun keabsahan data dalam penelitian ini menggunakan teknik triangulasi teknik dan triangulasi sumber. Hasil penelitian menunjukkan bahwa: (1) Peran Orang Tua dalam Penguatan Aktivitas Beribadah Anak Di Masa Pandemi Covid-19, antara lain: a) Sebagai motivator, b) Sebagai Uswah, c) Sebagai fasilitator, d) Sebagai mentor; (2) Langkah-langkah yang dilakukan orang tua ketika anak tidak menurut, antara lain: a) Bersikap tegas, b) Menerapkan aturan dan konsekuensi apabila anak melanggar, c) Meminta Bantuan Guru untuk Menasehati; (3) Faktor penghambat dalam Penguatan Aktivitas Beribadah Anak Di Masa Pandemi Covid-19, antara lain: a) Pengaruh teman sebaya, b) Pengaruh gadget, c) Mood anak yang naik turun. Orang tua diharapkan dapat membangun kerjasama yang baik dengan guru agar pembiasaan ibadah yang sebelumnya ada di sekolah dapat dilaksanakan di rumah secara maksimal.